The in-service education program of the five division pilot elementary schools of Cotabato II - Soriano, Leonides (Gutierrez) 1930-
The five division pilot elementary schools under study were established to provide a continuing and comprehensive program of in-service education for the district supervisors, principals, and teachers of Cotabato II. This research was conducted to determine how the respondents observed and appraised the program of the in-service education in relation to many factors. The data were primarily derived from the questionnaire responses, supplemented by the interview responses of the principals and supervisors. The findings of the study showed that the general aims and objectives of in-service education were not adequately implemented by the pilot elementary schools in Cotabato II.